Analisis Perbandingan Website E-Commerce Menggunakan Metode Webqual 4.0 - Agit Rian Rohmadan; Eko Setia Budi (STMIK Budi Darma, 2023)
Service quality is one of the top priorities for e-commerce providers to enhance public trust, especially in attracting customers to use e-commerce services more extensively. The current conditions, where efficiency and ease are demanded in all aspects, have made e-commerce transactions the preferred choice. With the increasing use of the internet in Indonesia, e-commerce service providers are competing to improve the quality of their services to provide user satisfaction, with the hope of increasing the number of transactions carried out by users. The abundance of e-commerce options has made it challenging for the public to differentiate which e-commerce services offer more comfort and security in transactions. To address this issue, researchers will present a comparison of the available e-commerce service quality. In evaluating e-commerce service quality based on end-users' perceptions, particularly the three largest e-commerce providers in Indonesia, namely Shopee, Lazada, and Tokopedia, researchers will collect data through questionnaires using the Webqual 4.0 method and the Smart PLS application for data analysis and predicting the relationships between variables in the questionnaire used. The aim of this study is to evaluate the service quality of these three e-commerce providers, Shopee, Lazada, and Tokopedia, and then map the evaluation results and provide information to the public about the trends in online transactions that occur in society.Based on the overall research using the Webqual 4.0 variables, the influence of the variables studied on user satisfaction is as follows: Shopee at 62.1 percent, Lazada at 70.7 percent, and Tokopedia at 63.5 percent.